Determination of acetate and formate in vegetable oils by ion chromatography after multivariate optimization of the extraction process using a Doehlert design - Fernández Campos, Adriana (2018)
In this work, we present the development of a method for the determination of acetate and formate in vegetable oils by ion chromatography with conductometric detection following their extraction from samples using a diluted KOH solution. The extraction procedure was optimized using a multivariate approach. The application of a 24 full factorial design showed that the mass of sample, extraction time, and KOH concentration presented significant influence on the extraction of both acetate and formate, whereas the temperature presented little influence on the process. As a result, we set the extraction temperature at 22 °C and performed the multivariate optimization of the other variables using a Doehlert design. The optimum conditions were: 4.8 g of sample, 8 mmol L−1 KOH solution and 19 min extraction time. Six samples of vegetable oils (soybean, corn, canola, sunflower and olive) were analyzed and recovery tests provided recovery percentages in the range of 82–118%.